Dominasi Atas Perempuan-Alam dalam Cerpen Sumur Karya Muna Masyari (Kajian Ekofeminisme) - Imawati, Endah; Retnosari, Putri (Universitas Negeri Surabaya, 2025)
This study aims to describe the deconstruction of excessive use of nature and the environment and ignoring the values ​​of local wisdom. This qualitative study uses ecofeminist thinking with the data source of the short story